A Holistic Conceptualization of Adult Learning and its Critiques of Selected Concepts and Theories - Baiyin Yang (Adult Education Research Conference, 2006)
This paper critically evaluates several contemporary concepts and theories of adult learning. Most of existing adult learning theories and conceptualizations tend to narrowly define knowledge and learning. Holistic learning theory provides an integrative framework that can be used adequately explain many propositions of major contemporary theories and concepts of adult learning.
Keywords: Holistic theory; adult learning; transformative learning